2022
DOI: 10.1128/jvi.01686-21
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Monoclonal Antibody against Human NTCP That Blocks Hepatitis B Virus Infection

Abstract: Hepatitis B virus (HBV) infects 240 million people worldwide. Current therapy profoundly suppresses HBV replication but requires long-term maintenance therapy. Therefore there is still a medical need for an efficient HBV cure. HBV enters host cells by binding via the preS1-domain of the viral L protein to the Na + /Taurocholate Cotransporting Polypeptide (NTCP). Thus, NTCP should be a key target for the development of anti-HBV therapeutics. Indeed, Myrcludex B, a synthetic form of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The inhibition of NTCP by N6HB426-20 depends on interacting with the 276th or 277th residue of ECL4 to sterically block the binding of HBV to ECL1 of NTCP. 89 In an experiment using PHHs as an infection model, N6HB426-20 effectively inhibited HBV infection with an IC 50 of 8 nM for the HBsAg concentration. Treatment with N6HB426-20 prevented HBV viremia in a mouse model for a longer time period.…”
Section: Macromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of NTCP by N6HB426-20 depends on interacting with the 276th or 277th residue of ECL4 to sterically block the binding of HBV to ECL1 of NTCP. 89 In an experiment using PHHs as an infection model, N6HB426-20 effectively inhibited HBV infection with an IC 50 of 8 nM for the HBsAg concentration. Treatment with N6HB426-20 prevented HBV viremia in a mouse model for a longer time period.…”
Section: Macromoleculesmentioning
confidence: 99%
“…Very recently, another mAb N6HB426-20 was established. The inhibition of NTCP by N6HB426-20 depends on interacting with the 276th or 277th residue of ECL4 to sterically block the binding of HBV to ECL1 of NTCP . In an experiment using PHHs as an infection model, N6HB426-20 effectively inhibited HBV infection with an IC 50 of 8 nM for the HBsAg concentration.…”
Section: Macromoleculesmentioning
confidence: 99%
“…To ensure the selection of binders against a native epitope, target proteins in multiple formulations/formats can be used alternately. For example, to engineer antibodies against Na + /taurocholate co-transporting polypeptide (NTCP), a key receptor for the hepatitis B virus, Takemori et al immunized NTCP-knockout mice with NTCP solubilized in detergent (1% DMM), reconstituted in liposomes, and expressed in transfected cells [38]. After 4-6 rounds of immunization, they screened the supernatants of hybridomas using a flow cytometric assay and identified mAb N6HB426, which efficiently inhibited HBV infection by binding to the extracellular domain of NTCP.…”
Section: Detergentsmentioning
confidence: 99%
“…The concentration that blocks HBV and HDV entry is 100-fold lower than that required to inhibit bile acid transport by NTCP ( Volz et al, 2013 ; Bogomolov et al, 2016 ; Cheng et al, 2021 ). At present, Myrcludex B has been approved in Europe for the treatment of patients with chronic HDV infection under the trade name Hepcludex ® ( Takemori et al, 2022 ). It has been reported that cyclosporin A (CsA), another peptide inhibitor that is usually used as an immunosuppressant in organ transplantation, as well as its analogs, can inhibit HBV infection by targeting NTCP and interfering with the interaction between preS1 and NTCP, thereby blocking HBV entry into hepatocytes ( Watashi et al, 2014b ; Nkongolo et al, 2014 ).…”
Section: Sodium Taurocholate Co-transporting Polypeptide As a Target ...mentioning
confidence: 99%
“…For example, MA18/7 and 2H5-A14 target the preS1 region and neutralize HBV infection ( Glebe et al, 2003 ; Li et al, 2017 ). In addition, a monoclonal antibody against NTCP—N6HB426-20—has been shown to recognize the extracellular domain of human NTCP (residues 276/277 at the tip of extracellular loop-4 of NTCP) and block HBV entry into human liver cells in vitro , while exerting substantially less of an inhibitory effect on bile acid uptake ( Takemori et al, 2022 ). With further improvements, this antibody may be a promising treatment option for patients with chronic hepatitis B.…”
Section: Sodium Taurocholate Co-transporting Polypeptide As a Target ...mentioning
confidence: 99%